Marketing Research for Market Share Development of Retail Feed Products in The Jabodetabek Area - Dudin, F.; Sumiati; D. A. Astuti; R. Fadilah (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Market research has the main function of understanding products, evaluating, predicting, knowing consumer needs and wants, so that companies can find product gaps that can be developed in the long term. This study aims to evaluate marketing strategies by understanding consumer behavior, evaluating consumer behavior and preferences (Understanding), and evaluating consumer needs and wants (Predicting). evaluating the current position of retail feed products (Controlling) and market share progress. The method used is primary data collection through surveys, interviews and direct observations conducted at Shops or Poultry Shops in the Jabodetabek area, while secondary data is taken from the sales report sources at PT New Hope Indonesia (NHI). Based on information from the results of market research, it can be a basis for determining what retail feed products need to be marketed, namely retail feed for native broiler chickens, roosters, hybrid meat ducks and quail, this is proven by the sales volume of retail feed products, namely native chickens, increased by 8-10%, roosters 107%, meat ducks 20%, and quail 20% compared to 2021 when market research was conducted. Theconclusion of the market research conducted indicates that a research-based approach can help feed companies to be more adaptive to market dynamics and consumer needs, thereby supporting market share growth in the Jabodetabek area.